Reaksi Pasar Modal terhadap Pengumuman Buyback Saham di Bursa Efek Indonesia: Analisis Abnormal Return Periode 2020-2025 - Anjudia Samosir; Lija Romauli Hutajulu; Didik Gunawan; Willy Cahyadi (Jurnal Kajian dan Penelitian Umum, 2026)
This study analyzes market reactions to stock buyback announcements on the IDX for the 2020-2025 period, focusing on the differences in AAR and ATVA before and after the announcement. The event study method used 198 samples (purposive sampling), with an 11-day event window (D-5 to D+5). AAR was calculated using a market-adjusted model, and ATVA was based on the volume ratio. The Wilcoxon test was used because the data was not normal. Results: AAR increased descriptively (-0.07262 to 0.08903), ATVA increased (2.42976 to 3.56669), but the Wilcoxon test showed no significance (AAR p=0.608; ATVA p=0.158). H₁ and H₂ were rejected, meaning the market did not respond significantly. This study tests Signaling Theory and the semi-strong form of the EMH in emerging markets during prolonged macroeconomic shocks and extends the empirical evidence to 2025. The results are expected to indicate whether the Indonesian capital market reacts significantly (semi-strong form information efficiency), as indicated by positive and significant abnormal returns around the announcement window, or whether it exhibits no significant response. The findings of this study have important implications for issuers in determining strategic corporate timing and for investors in formulating trading strategies to capitalize on event-driven momentum in emerging markets.